Design of spread foundations on rock masses according to Eurocode 7 - Miranda, Tiago F. S. (2012)
In Eurocode 7 (EC7), some guidelines are provided for the design of spread foundations built on rock masses. Moreover, a method for the calculation of the bearing capacity for this type of foundations is suggested. However, it does not take into account important factors that influence the bearing capacity of foundation, which can be an important limitation of the method. In this work the EC7 method is presented along with two other methods that can be found in literature. They are applied to two simple examples and the results are analysed. High dispersion was found in the results meaning that the EC7 method should be used with caution even for very simple cases.